ANALISIS PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN MOTIVASI SEBAGAI VARIABEL INTERVENING SELAMA WORK FROM HOME TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN MUSI RAWAS UTARA - Pujiyarti Pujiyarti; Sardiyo Sardiyo; Noorchamid Ustadi (LPPM UNIVERSITAS BINA INSAN, 2021)
This study examines the workload, work environment and motivation as intervening variables on the performance of employees in the North Musi Rawas Regency Education Office. This research was conducted with a population of 126 respondents. The results showed that partially the workload, work environment and motivation had a direct effect on employee performance. However, the indirect effect is greater than the direct effect, namely workload and work environment mediated by motivation as an intervening variable on employee performance. The management implication is that the workload and work environment of employees are the benchmarks in increasing work motivation so that it affects employee performance.